2021
DOI: 10.1038/s41598-021-87082-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for poor outcome in childhood tuberculous meningitis

Abstract: Tuberculous meningitis (TBM) remains a serious disease for children and its risk factors of poor outcome remain unclear. Therefore, a retrospective study was conducted aiming to investigate the risk factors associated with poor outcome of childhood TBM. Between January 2006 and December 2019, consecutive children patients (≤ 15 years old) who had a diagnosis of TBM were included for the analysis. The demographic, clinical, laboratory, and radiographic data were collected from the electronic medical records ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
2
10
2
Order By: Relevance
“…Moreover, limited techniques for effective TBM diagnosis in children, such as Xpert Ultra, are currently available (7). Two key factors are responsible for the diagnostic limitations in childhood TBM: (1) cerebrospinal fluid (CSF) is a paucibacillary specimen type and (2) TB in children is often paucibacillary. In addition, TBM is difficult to treat and often responds poorly to conventional TB treatment (8,9).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, limited techniques for effective TBM diagnosis in children, such as Xpert Ultra, are currently available (7). Two key factors are responsible for the diagnostic limitations in childhood TBM: (1) cerebrospinal fluid (CSF) is a paucibacillary specimen type and (2) TB in children is often paucibacillary. In addition, TBM is difficult to treat and often responds poorly to conventional TB treatment (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…The Marais classification criteria are based on Thwaites' Index, which has previously shown good performance (12)(13)(14). However, these criteria are associated with a number of disadvantages that need to be addressed: (1) the difference between childhood and adult TBM is not fully considered, (2) the scoring system is presented as a personal view and lacks sufficient data to support its efficiency, and (3) insufficient information is available on the utility of the criteria in China.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of access to supportive care and neurorehabilitation in low-resourced, TB-endemic settings further exacerbate poor outcomes [97]. Whilst reasons for poor outcomes are likely to be multifactorial, diagnosis before the onset of coma remains the most crucial factor predicting survival and favourable outcomes [98].…”
Section: Discussionmentioning
confidence: 99%
“…11–13 Moreover, advanced stage of TBM, 4 , 5 , 12–15 coma at presentation, delay in diagnosis and treatment, and complications such as hydrocephalus are significantly associated factors. 16–19 Few studies in central Ethiopia have revealed that TBM in children leads to poor treatment outcomes. For example, TBM-related death ranges from 14% to 43%, and neurological deficits range from 28% to 47%.…”
Section: Introductionmentioning
confidence: 99%